EFEKTIFITAS PERATURAN DAERAH KOTA MAKASSAR NOMOR 6 TAHUN 2013 DALAM PEMENUHAN HAK DASAR PENDIDIKAN PENYANDANG DISABILITAS DI KOTA MAKASSAR - Firman Umar; Nur Syarif Ramadhan (Universitas Negeri Makassar, 2018)
This study aims to determine: (1) The fulfillment of basic rights to education for Persons with Disabilities in Makassar based on Local Regulation Makassar City No. 6 of 2013, (2) Obstacles encountered in obtaining the basic right of education of persons with disabilities in the city of Makassar, (3 ) the right solution to overcome the obstacles encountered in obtaining the basic right of education of persons with disabilities in the city of Makassar. This research is a study that used a qualitative descriptive approach, which is where the primary data source being informers are students with disabilities the high school level, students with disabilities S1, officials of Education Department of Makassar, members of Parliament of Makassar, the Management Organization disabilities, Pembina NGOs and Parents persons with disabilities. The data collection procedures used were interviews and documentation. While the analysis of the data used is descriptive analysis. The results showed that: (1) Makassar City Government has sought the fulfillment of the basic right to education for persons with disabilities in the city of Makassar. it is evidenced with the local regulations require every institution in which education in the city of Makassar to provide opportunities for persons with disabilities to education. The effect of the presence of these regulations is at the moment with disabilities have been able to attend school at any educational institutions both at school SLB, Regular schools and universities. (2) they encountered several obstacles that obtained with disabilities in getting the right to education that is still no educational establishments are not willing to accept persons with disabilities to attend regular schools, educational facilities are not accessible for persons with disabilities and there are educators at regular schools who do not understand in dealing with students with disabilities. (3) to overcome these obstacles, the government should socialize more about the policies that guarantee basic rights of education of persons with disabilities in educational institutions that are still not willing to accept students with disabilities. In addition, the government should identify the persons with disabilities who attend regular school, then allocate the budget for the procurement of infrastructure and training of educators in dealing with students with disabilities in regular schools and universities.